TRADISI ALE RASA BETA RASA SEBAGAI PERAWAT KERUKUNAN UMAT BERAGAMA DI INDONESIA TIMUR - Abu Abu Muslim (Pascasarjana IAIN Ambon, 2020)
Study of the Ale Rasa Beta Rasa, made by combining descriptive approach qualitative research-based reading of the phenomenon-a phenomenon that occurs in people with a review of documents that depicted in the news and social media, is a form of 'invitation' top scientific inspiration of local wisdom that develops in a the public system to the next can be 'used' to create and care for religious harmony, especially in Eastern Indonesia. This study saw that the real Ale Rasa Beta Rasa, is a symbolization nurse harmony if dijewantahkan is positive is the embodiment of the values of local unifying social is also found in some areas in eastern Indonesia, although in the form and articulation of different, but the spirit and the same meaning, ie, as the momentum of prevention of all forms of 'invitation' negative developed in the community, and turn it into a 'taste' the humanity and justice, in the embodiment of the spirit of harmony.